(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The new physical education (PE) curriculum in Estonia aimed to support pupils’ physical literacy and health. It was accepted by the Estonian Government in 2023 and in the study year 2024/2025 the schools had to start to implement this. Previous curriculums were all sport-centred and the new concept was a big change. Project or Policy Description: The development of the curriculum started in 2016 with composing a document describing the situation of PE. The period of 2017–2019 was the development process led by the Ministry of Education and Science. The main partner was the Institute of Sport and Physiotherapy, University of Tartu, but the working group included many PE teachers. Organisations and teachers had many opportunities to give feedback. Still, it took four years because of the political situation to approve it. The national curriculum brings out five outcome areas: movement skills, physical activity, health and physical fitness, movement and culture, and mind and body. There is also a strong focus on creating the learning environment that supports pupils’ basic psychological needs. Implementation of the curriculum was supported by workshops for the teachers, new teaching materials, and homepage development. The PE teacher curriculum at the university level was changed. In recent years, there have been numerous coverages by the media about PE change. In year 2024, the state supported Estonian general education schools with three million euros to buy necessary sport equipment. Evaluation related to the implementation of the curriculum has been realised through different research activities. For example, every year the Ministry of Education and Science carries out a survey about pupils’ satisfaction with the school, including some questions about PE. But there is a need for more complex, targeted, and thorough surveys to examine how schools have implemented the curriculum and how pupils perceive the change, assessing its influence on health-related behaviour. Additional dissemination is done through regular teacher workshops, presentations in public seminars, and through media. Conclusion: The process of developing and implementing the new PE curriculum was long and this experience can be valuable for countries or interest groups developing their own health enhancing and physical literacy oriented PE curriculum. Keywords: Children, adolescents, reform, transformation, health promotion, students, learning